The Occupational Risk Factors Associated with Hip Osteoarthritis in Agricultural Communities in Jember - Ristianto Yoga Pratama; Laksmi Indreswari; Ika Rahmawati Sutejo (Universitas Wijaya Kusuma Surabaya, 2023)
Occupational risk factors have a significant effect on osteoarthritis (OA). It has been studied before. However, no one has looked into occupational risk for the prevalence of hip OA in agricultural communities of Jember. This study aims to determine the relationship between risk factors (gender, age, body mass index, work history, work posture, length of work, and length of work) and hip OA incidence. This analytical observational study uses a cross-sectional design at Doctor Soebandi Jember's Regional Hospital and Jember Clinic Hospital, East Java-Indonesia. This study included all hip OA patients who visited the orthopedic clinic from January 2020 to December 2021. Thirty-six patients and 18 samples had hip OA (50%). Of eighteen subjects with hip OA, 14 were female (77.8%), 12 were aged ≥55 years old (66.7%), 12 were pre-obese with BMI >25 (66.7%), 14 had a history of lifting heavy weights (77.8%), 16 related to bending working posture (88.9%), 13 had a long working year >10 years (72.7%), 11 had a long working duration >44 hours (61.1%), 9 worked as a housewife and farmers (50%). %). A significant relationship of hip OA was observed with gender (p-value 0.003), age (p-value 0.019), work posture (p-value 0.002), length of work (p-value 0.003), and duration of work (p-value 0.018) based on contingency coefficient statistical analysis. We can conclude that the significant risk factors related to hip osteoarthritis in agricultural areas are gender, age, work posture, work length, and work duration.